Ultra-Long Transfers for Endovascular Thrombectomy—Mission Impossible?: The Australia-New Zealand Experience. Issue 1 (23rd November 2022) - Garcia-Esperon, Carlos; Wu, Teddy Y.; Carraro do Nascimento, Vinicius; Yan, Bernard; Kurunawai, Craig; Kleinig, Tim; Selkirk, Gregory; Blacker, David; Barber, P. Alan; Ranta, Annemarei; Cervera, Alvaro; Wong, Andrew; et al.
Abstract : Background: Endovascular thrombectomy (EVT) access in remote areas is limited. Preliminary data suggest that long distance transfers for EVT may be beneficial; however, the magnitude and best imaging strategy at the referring center remains uncertain. We hypothesized that patients transferred >300 miles would benefit from EVT, achieving rates of functional independence (modified Rankin Scale [mRS] score of 0–2) at 3 months similar to those patients treated at the comprehensive stroke center in the randomized EVT extended window trials and that the selection of patients with computed tomography perfusion (CTP) at the referring site would be associated with ordinal shift toward better outcomes on the mRS. Methods: This is a retrospective analysis of patients transferred from 31 referring hospitals >300 miles (measured by the most direct road distance) to 9 comprehensive stroke centers in Australia and New Zealand for EVT consideration (April 2016 through May 2021). Results: There were 131 patients; the median age was 64 [53–74] years and the median baseline National Institutes of Health Stroke Scale score was 16 [12–22]. At baseline, 79 patients (60.3%) had noncontrast CT+CT angiography, 52 (39.7%) also had CTP. At the comprehensive stroke center, 114 (87%) patients underwent cerebral angiography, and 96 (73.3%) proceeded to EVT. At 3 months, 62 patients (48.4%) had an mRS score of 0 to 2 and 81 (63.3%) mRS score of 0 to 3. CTP selection at the referring site was not associated with better ordinal scores on the mRS at 3 months (mRS median of 2 [1–3] versus 3 [1–6] in the patients selected with noncontrast CT+CT angiography, P =0.1). Nevertheless, patients selected with CTP were less likely to have an mRS score of 5 to 6 (odds ratio 0.03 [0.01–0.19]; P <0.01). Conclusions: In selected patients transferred >300 miles, there was a benefit for EVT, with outcomes similar to those treated in the comprehensive stroke center in the EVT extended window trials. Remote hospital CTP selection was not associated with ordinal mRS improvement, but was associated with fewer very poor 3-month outcomes.